Prevalence and severity of caries in 3-12-year-old children from three districts with different fluoridation histories in Araraquara, SP, Brazil - Dini, E. L. [UNESP]; Holt, R. D.; Bedi, R. (My University, 1998)
Objective: To determine the prevalence and severity of caries in 3-12-year-old children in three districts of the city of Araraquara, Design: An epidemiological survey was carried out by trained and calibrated examiners in 1995 and 1996, using the WHO diagnostic criteria. Setting: Two districts, Araraquara and Vila Xavier had been fluoridated since 1963 and one, Gavião Peixoto, since 1994. Subjects: The study included 1,191 children from Araraquara, 653 from Vila Xavier and 652 from Gavião Peixoto. Outcome measures: Prevalence of caries, dmft, dmfs, DMFT and DMFS indices. Results: Results showed moderate caries experience in all three districts. Differences between districts in relation to fluoridation history were particularly obvious in primary teeth. In 3-4-year-old children, one third of those in Araraquara and Vila Xavier had some caries experience compared to 58% in Gavião Peixoto. In permanent teeth, 20% or less of the mean DMFT was made up of untreated decay in Araraquara and Vila Xavier whereas in Gaviao Peixoto it made up between 50 and 57% of values in 7-12-year-old children. Conclusions: The prevalence and severity of caries was lower in dentitions of children from the districts fluoridated since 1963. Improvements are likely in the future in Gaviao Peixoto as the benefit of fluoridation continues but additional means of promoting oral health are needed in all three districts.
Keywords: Caries prevalence; Epidemiology; Water fluoridation; age; analysis of variance; Brazil; child; comparative study; deciduous tooth; dental caries; fluoridation; health promotion; health survey; human; pathology; preschool child; prevalence; statistics; tooth; world health organization; Age Factors; Analysis of Variance; Child; Child, Preschool; Dental Caries; DMF Index; Fluoridation; Health Promotion; Humans; Prevalence; Tooth; Tooth, Deciduous; World Health Organization